Temporal change in abundance of potential nesting cavities for wood ducks (Aix sponsa) in Northern Minnesota, United States - Berdeen, James B.; Nelson, Mark D.; Zlonis, Edmund J.; Giudice, John H. (Frontiers in Forests and Global Change, 2022)
Wood duck females often nest in tree cavities located in large-diameter deciduous trees. Temporal changes in forest age and composition during recent decades may have influenced the abundance of stems with suitable nesting cavities in the forested portion of Northern MN, United States. Thus, we ascertained whether temporal changes in the abundance of such stems occurred in this area during six Forest Inventory and Analysis (FIA) evaluation cycles (i.e., 1977 to 2015–2019). We used FIA data and independently estimated proportions of stems with suitable cavities in different tree-species, health-status, and diameter classes to estimate change in the abundance of such stems at three spatial scales. These spatial scales increased in areal extent from a study area to three ecological subsections to the Laurentian Mixed Forest ecological province. We used a Bayesian analytical approach to accommodate changes in FIA protocols among cycles. Both the abundance of stems with suitable cavities and an attribute associated with cavity occurrence changed during the analysis period, but findings were not entirely consistent among spatial scales. The estimated abundance of both suitable stems overall and those of late-successional tree species generally increased at all scales during the analysis period. Since 1990, increases in the abundance of health-impacted stems that were suitable for nesting occurred at all spatial scales. Our estimated densities of suitable stems during the 2005–2009 (1.20 [85% CrI: 1.04–1.39] suitable stems / ha) and 2015–2019 cycles (1.41 [85% CrI: 1.21–1.63] suitable stems / ha) were substantially greater than the <0.25 and 0.25–0.49 suitable stems / ha another study predicted would occur in Northern Minnesota during 2008 and 2018, respectively. Our results can inform forest management decisions and research directions for follow-up studies of nesting wood ducks.